NMR metabolic profiling of lipopolysaccharide-induced mice sepsis and the treatment effects of berberine. Issue 53 (13th May 2016) - Li, Pei; Liao, Shanting; Wang, Junsong; Xu, Dingqiao; Zhang, Qian; Yang, Minghua; Kong, Lingyi
Abstract : 1 H NMR metabolomics to study lipopolysaccharide-induced mice sepsis and the treatment effects of berberine. Abstract : Sepsis is a complex syndrome arising from a systemic inflammatory response to infection. Despite its prevalence in clinical practice, its pathophysiology is still poorly understood, especially in a holistic view, which is essential considering its global nature. With obvious anti-bacterial and anti-inflammatory activities, berberine could improve the survival of sepsis mice and attenuate tissue injury. In this work, a lipopolysaccharide induced sepsis mice model was established to investigate the metabolic events of sepsis and the protection of berberine. In conjunction with histopathological inspection, survival rate, the mRNA expression analysis of related genes and biochemical assay, 1 H NMR-based metabolomics approach was applied in this study to explore the toxicities of lipopolysaccharides (LPSs) and the treatment effect of berberine on LPS-induced sepsis. Principal component analysis (PCA) and orthogonal partial least squares-discriminant analysis (OPLS-DA) were performed to excavate the metabolic disturbance of sepsis, concerning inflammation, oxidative stress, energy metabolism, and metabolisms of amino acids and nucleic acids, which could be greatly ameliorated by berberine, consistent with the results of biochemical and histopathological inspections and the mRNA expression analysis of related genes. This integrated metabolomics study provided a powerful and highly effective approach to globally characterize the metabolic status of an organism, to understand the intricate pathology of the disease, and to evaluate the holistic efficacy of a therapy.